The Challenges Encountered by Zakat Recipients Entrepreneurs - Hashim, Norashidah; Mohamad, Armanurah; Othman, Azizah (Lembaga Zakat Negeri Kedah, 2020)
Zakat recipients can develop the family economy and get out of poverty by engaging in entrepreneurial activities. This entrepreneurial activity needs support from many authorities and concerned parties. This paper discusses the issues and opportunities faced by micro-size business entrepreneurs who have received assistance from the Kedah Zakat Authority through the Jayadiri Assistance program. The findings of this study were obtained through semistructured interviews and observations of 49 asnaf entrepreneurs in the state of Kedah that engaged in micro-size business as an effort to earn for living. The findings show an increase in their income since engaging in entrepreneurship activities. However, there are some issues such as lack of skills and knowledge in business management especially financial aspects, operation of production and marketing activities. Most interviewees have problems growing their business due to lack of equipment, labor-intensive, lack of capital, lack of focus on a product, limited space, hygiene issues, and many more. They have the opportunity and the potential to grow their business as they have regular customers and products that meet the needs of their customers' demand and taste. Marketing strategy using online marketing can be implemented only if the entrepreneur can meet demand by increasing production capacity. It is suggested that careful monitoring, skills development, and knowledge interventions from those involved in this Jayadiri program can increase the potential for these aspiring entrepreneurs to become zakat payers in the future